Fasciola hepatica excretory-secretory products induce CD4+T cell anergy via selective up-regulation of PD-L2 expression on macrophages in a Dectin-1 dependent way - Guasconi, Lorena (2015)
Fasciola hepatica excretory-secretory products (FhESP) induce immunomodulatory effects on macrophages. Previously, we demonstrated that these effects are dependent on Dectin-1. Therefore, the aim of this study was to determine how this affects the CD4 T-cells immune response.We observed that FhESP induce an increased expression of PD-L2 in macrophages via Dectin-1. Furthermore, in co-cultures with CD4 T-cell we observed a suppressive effect on proliferative response, down-modulation of IFN-γ and up-modulation of IL-10 via Dectin-1 on macrophages. These results suggest that FhESP induce T-cell anergy via selective up-regulation of PD-L2 expression on macrophages in a Dectin-1 dependent way.